2010
DOI: 10.1186/1471-2458-10-536
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in dissatisfaction with sexual life in patients with type 2 diabetes in a Swedish town

Abstract: BackgroundThe first aim of this study was to analyze whether self-reported satisfaction with one's sexual life was associated with ethnicity (Swedish and Assyrian/Syrian) in patients with type 2 diabetes. The second was to study whether the association between satisfaction with one's sexual life and ethnicity remained after controlling for possible confounders such as marital status, HbA1c, medication, and presence of other diseases.MethodsThis cross-sectional, questionnaire-based study was conducted at four p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…To the best of our knowledge, this is the second study on self-reported sexual health and the first on self-reported sexual dysfunction in a population consisting of Assyrians/Syrians and Swedes. Our first study in the same Assyrian/Syrian sample investigated dissatisfaction with one’s sexual life compared to Swedish-born patients with type 2 diabetes [13]. That study showed no significant ethnic differences in the dissatisfaction with one’s sexual life [13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, this is the second study on self-reported sexual health and the first on self-reported sexual dysfunction in a population consisting of Assyrians/Syrians and Swedes. Our first study in the same Assyrian/Syrian sample investigated dissatisfaction with one’s sexual life compared to Swedish-born patients with type 2 diabetes [13]. That study showed no significant ethnic differences in the dissatisfaction with one’s sexual life [13].…”
Section: Resultsmentioning
confidence: 99%
“…Our first study in the same Assyrian/Syrian sample investigated dissatisfaction with one’s sexual life compared to Swedish-born patients with type 2 diabetes [13]. That study showed no significant ethnic differences in the dissatisfaction with one’s sexual life [13]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a multifactorial condition, ED is known to be associated with age, ethnicity, and comorbid conditions. 10 11 12 Some studies suggested that the effectiveness of PDE5-Is seem to be better in Caucasians than Asians, 13 but similar among black American, Hispanic American men and Caucasians. 14 15 Other factors like body mass index (BMI), disease severity/duration, etiology, and comorbidity may also influence the treatment effects, but the evidence is rather controversial.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable disagreement in the literature in regards to female sexual satisfaction in diabetes, which could vary according to the study's design, and the participants' age, ethnicity, and partner's sexual performance (12,15,26,28).…”
mentioning
confidence: 99%